Early skin-to-skin contact for mothers and their healthy newborn infants - Moore, Elizabeth R; Bergman, Nils; Anderson, Gene C; Medley, Nancy (Cochrane database of systematic reviews, 2016)
Mother-infant separation post birth is common. In standard hospital care, newborn infants are held wrapped or dressed in their mother's arms, placed in open cribs or under radiant warmers. Skin-to-skin contact (SSC) begins ideally at birth and should last continually until the end of the first breastfeeding. SSC involves placing the dried, naked baby prone on the mother's bare chest, often covered with a warm blanket. According to mammalian neuroscience, the intimate contact inherent in this place (habitat) evokes neuro-behaviors ensuring fulfillment of basic biological needs. This time frame immediately post birth may represent a 'sensitive period' for programming future physiology and behavior. To assess the effects of immediate or early SSC for healthy newborn infants compared to standard contact on establishment and maintenance of breastfeeding and infant physiology. We searched the Cochrane Pregnancy and Childbirth Group's Trials Register (17 December 2015), made personal contact with trialists, consulted the bibliography on kangaroo mother care (KMC) maintained by Dr Susan Ludington, and reviewed reference lists of retrieved studies. Randomized controlled trials that compared immediate or early SSC with usual hospital care. Two review authors independently assessed trials for inclusion and risk of bias, extracted data and checked them for accuracy. Quality of the evidence was assessed using the GRADE approach. We included 46 trials with 3850 women and their infants; 38 trials with 3472 women and infants contributed data to our analyses. Trials took place in 21 countries, and most recruited small samples (just 12 trials randomized more than 100 women). Eight trials included women who had SSC after cesarean birth. All infants recruited to trials were healthy, and the majority were full term. Six trials studied late preterm infants (greater than 35 weeks' gestation). No included trial met all criteria for good quality with respect to methodology and reporting; no trial was successfully blinded, and all analyses were imprecise due to small sample size. Many analyses had statistical heterogeneity due to considerable differences between SSC and standard care control groups. Results for womenSSC women were more likely than women with standard contact to be breastfeeding at one to four months post birth, though there was some uncertainty in this estimate due to risks of bias in included trials (average risk ratio (RR) 1.24, 95% confidence interval (CI) 1.07 to 1.43; participants = 887; studies = 14; I² = 41%; GRADE: moderate quality). SSC women also breast fed their infants longer, though data were limited (mean difference (MD) 64 days, 95% CI 37.96 to 89.50; participants = 264; studies = six; GRADE:low quality); this result was from a sensitivity analysis excluding one trial contributing all of the heterogeneity in the primary analysis. SSC women were probably more likely to exclusively breast feed from hospital discharge to one month post birth and from six weeks to six months post birth, though both analyses had substantial heterogeneity (from discharge average RR 1.30, 95% CI 1.12 to 1.49; participants = 711; studies = six; I² = 44%; GRADE: moderate quality; from six weeks average RR 1.50, 95% CI 1.18 to 1.90; participants = 640; studies = seven; I² = 62%; GRADE: moderate quality).Women in the SCC group had higher mean scores for breastfeeding effectiveness, with moderate heterogeneity (IBFAT (Infant Breastfeeding Assessment Tool) score MD 2.28, 95% CI 1.41 to 3.15; participants = 384; studies = four; I² = 41%). SSC infants were more likely to breast feed successfully during their first feed, with high heterogeneity (average RR 1.32, 95% CI 1.04 to 1.67; participants = 575; studies = five; I² = 85%). Results for infantsSSC infants had higher SCRIP (stability of the cardio-respiratory system) scores overall, suggesting better stabilization on three physiological parameters. However, there were few infants, and the clinical significance of the test was unclear because trialists reported averages of multiple time points (standardized mean difference (SMD) 1.24, 95% CI 0.76 to 1.72; participants = 81; studies = two; GRADE low quality). SSC infants had higher blood glucose levels (MD 10.49, 95% CI 8.39 to 12.59; participants = 144; studies = three; GRADE: low quality), but similar temperature to infants in standard care (MD 0.30 degree Celcius (°C) 95% CI 0.13 °C to 0.47 °C; participants = 558; studies = six; I² = 88%; GRADE: low quality). Women and infants after cesarean birthWomen practicing SSC after cesarean birth were probably more likely to breast feed one to four months post birth and to breast feed successfully (IBFAT score), but analyses were based on just two trials and few women. Evidence was insufficient to determine whether SSC could improve breastfeeding at other times after cesarean. Single trials contributed to infant respiratory rate, maternal pain and maternal state anxiety with no power to detect group differences. SubgroupsWe found no differences for any outcome when we compared times of initiation (immediate less than 10 minutes post birth versus early 10 minutes or more post birth) or lengths of contact time (60 minutes or less contact versus more than 60 minutes contact). Evidence supports the use of SSC to promote breastfeeding. Studies with larger sample sizes are necessary to confirm physiological benefit for infants during transition to extra-uterine life and to establish possible dose-response effects and optimal initiation time. Methodological quality of trials remains problematic, and small trials reporting different outcomes with different scales and limited data limit our confidence in the benefits of SSC for infants. Our review included only healthy infants, which limits the range of physiological parameters observed and makes their interpretation difficult.